2021
DOI: 10.3389/fpls.2021.628521
|View full text |Cite
|
Sign up to set email alerts
|

Improving Nitrogen Use Efficiency Through Overexpression of Alanine Aminotransferase in Rice, Wheat, and Barley

Abstract: Nitrogen is an essential nutrient for plants, but crop plants are inefficient in the acquisition and utilization of applied nitrogen. This often results in producers over applying nitrogen fertilizers, which can negatively impact the environment. The development of crop plants with more efficient nitrogen usage is, therefore, an important research goal in achieving greater agricultural sustainability. We utilized genetically modified rice lines over-expressing a barley alanine aminotransferase (HvAlaAT) to hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 95 publications
1
22
0
Order By: Relevance
“…Garnett et al (2013) found no biomass differences among wildtype and maize AlaAT transgenic plants in a hydroponic system under different N rates (0.5 and 2.5 mM N). Tiong et al (2021) found similar results for rice plants expressing OsAnt1:HvAlaAT grown in a hydroponics system. This similarity suggested that hydroponic systems provide steady N supplies even at low concentrations.…”
Section: Efficacy Test For the Nue Of The T1 Transgenic Generation Containing Lealaat Genesupporting
confidence: 69%
See 3 more Smart Citations
“…Garnett et al (2013) found no biomass differences among wildtype and maize AlaAT transgenic plants in a hydroponic system under different N rates (0.5 and 2.5 mM N). Tiong et al (2021) found similar results for rice plants expressing OsAnt1:HvAlaAT grown in a hydroponics system. This similarity suggested that hydroponic systems provide steady N supplies even at low concentrations.…”
Section: Efficacy Test For the Nue Of The T1 Transgenic Generation Containing Lealaat Genesupporting
confidence: 69%
“…Selvaraj et al (2016) discovered a limited or no increase in the biomass of the 43-day old plants of OsAnt1:HvAlaAT transgenic lines with a NERICA4 background under low N conditions. These results implied that during vegetative growth, the biomass of the transgenic lines may moderately and nonsignificantly increase and is then accumulated throughout the growth stages, resulting in a significant increase in biomass and seed yield (Tiong et al, 2021).…”
Section: Efficacy Test For the Nue Of The T1 Transgenic Generation Containing Lealaat Genementioning
confidence: 89%
See 2 more Smart Citations
“…The HvAlaAT expression increased the biomass in sugarcane [ 124 ] and the vegetative biomass and grain yield in wheat, yet it did not change the phenotype of sorghum [ 126 ]. As shown by a recent study [ 128 ], a transfer of a gene combination of OsAnt1::HvAlaAT to rice, wheat and barley increased biomass and yield. Researchers found significant changes in carbohydrate metabolism, which includes glycolysis and the TCA cycle, and suggested that the increased production of energy resulted in increased N assimilation.…”
Section: Genetic Engineering Of Nitrogen Metabolismmentioning
confidence: 94%